Tunable CPW Ring Resonator-Based Bandpass Filters Utilizing RF MEMS Varactors - Dast, Ahlam Mohammad Ebrahim Pish (2017)
A Master of Science thesis in Electrical Engineering by Ahlam Mohammad Ebrahim Pish Dast entitled, "Tunable CPW Ring Resonator-Based Bandpass Filters Utilizing RF MEMS Varactors," submitted in January 2017. Thesis advisor is Dr. Maher Bakri Kassem. Soft and hard copy available.